IDENTIFICATION OF G10398A VARIAN OF ND3 GENE MITHOCONDRIA DNA IN BREAST CANCER PATIENT - Tianing, Ni Wayan (Medicina, 2013)
ND3  gene is a mitochondria DNA gene which code for NADH dehydrogenase enzime, part of complex 1  respiratory  chain  oxidation  and  involved  in  phosphorilation  prosess  to  synthesize ATP  (Adenosin Triphosphat). The present of G10398A variant at mtDNA result in changing the amino acid code for alanine (GCC) to threonine (ACC). This changing induce elevation the ROS (Reactive Oxygen Species) concentration in mitochondria. ROS can cause oxidation of DNA, mutation of DNA,oxidative stress and cancer. The other effect of ROS can affect redox-cycling estrogen metabolism. Individual   with G10398A variant has   60% risk for breast cancer.  The purpose of this research are to identify G10398A variant and its proportion in ND3 gene with non experimental descriptive method within 32 samples and 5 control. This research has done with sequence of steps with an isolation and total DNA amplification electrophoresis, sequencing and analysis by comparing with gene bank.  This research identify G10399A variant that causes changing code from serine (AGC) amino acid in to asparagines (A A C) in 16 samples. Another variant found in this research is C10401T variant the cause changing in codon that code from arginin (CGA) in to triptopan (TGA) within 14 samples. In the control groups 2 samples identify with G10399A variant, 2 samples with C10401T and 1 control match like gene-bank . For this research, ND3 gene homology that was amplified found in the average of  96%.
Keywords: ND3 gene, G10398A variant and breast cancer